Desain Dan Analisis Turbin Uap Aksial Pada Aplikasi Pembangkit Listrik Tenaga Uap Skala Rendah (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2025)
Electrification issues in remote areas of Indonesia remain a significant challenge, primarily due to infrastructure limitations and the high operational costs of fossil fuel-based power plants. This study aims to design and analyze a small-scale axial steam turbine ( 1 kW) suitable for biomass-fueled steam power generation systems. The design process utilized SolidWorks 2022, supported by numerical simulations to evaluate structural strength, thermal efficiency, and fluid flow characteristics. Simulation results show that the maximum stress on components remains well below the material yield strength, while the system's estimated efficiency reaches 65–70%. The final design includes optimized configurations of blades, rotor, nozzle, and steam flow distribution. This study demonstrates that a CAD-based approach enables the development of efficient and technically feasible micro steam turbines for use in resource-constrained regions.